Bersuara Lewat Foto: Menyingkap Pengalaman Masyarakat terhadap Industri Migas - Alfrendi, Jonathan (Universitas Padjadjaran, 2025)
This article aims to explain the influence and impact of the oil and gas industry on communities based on their life experiences, which were studied using the photovoice method. Data collection was conducted through participant observation around the oil and gas industry area in Tapung Hulu District, Riau. Through the presentation of photographs taken by informants (photovoice), this study provides a space for the community to voice their experiences visually, document their daily realities, and convey them so that they can be heard and followed up by policy makers. The findings show that the presence of the oil and gas industry has opened up job opportunities for women, but at the same time has given rise to various social and environmental problems, such as the vulnerability of buildings to cracks and limited access to clean water. In addition, the findings also reveal that the corporate social responsibility (CSR) programs that are being implemented are still charitable in nature and are not yet oriented towards sustainable social empowerment. This article contributes to the anthropological literature on the relationship between the oil and gas industry and local communities by offering a photovoice methodological approach to connect the experiences of communities in a contextual and reflective manner.